The Influence of Social Media Marketing on Purchase Decisions With Brand Awareness As Mediation (Study on Truffle Belly Jimbaran) - Simamora, Ezra Chatarina; Suparna, Gede (Dinasti International Journal of Economics, Finance & Accounting, 2025)
Social media marketing is a marketing strategy that leverages social media platforms to build relationships with consumers, enhance brand awareness, and drive purchasing decisions. This study aims to analyze the role of brand awareness in mediating the influence of social media marketing on purchasing decisions among consumers of Truffle Belly Jimbaran. The study involved 100 respondents selected using the purposive sampling method. Data were collected through online questionnaires and analyzed using path analysis techniques, the Sobel test, and the VAF test. The results indicate that all hypotheses were supported. Social media marketing has a significant positive impact on purchase decisions; social media marketing has a significant positive impact on brand awareness; brand awareness has a significant positive impact on purchase decisions; and brand awareness is proven to partially mediate the influence of social media marketing on purchase decisions. The theoretical implications of this research support the S-O-R (Stimulus-Organism-Response) theory and previous studies on consumer behavior. The practical implications suggest that Truffle Belly Jimbaran should enhance the quality and consistency of promotional content on social media, strengthen brand awareness among consumers, and optimize digital marketing strategies to maintain stability and increase sales.